Scholarly communications competencies: open access training for librarians. Issue 7 (13th July 2015) - Rodriguez, Julia E
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to describe one example of an academic library using existing internal expertise and targeted events to provide training for liaison librarians in support of new scholarly communication initiatives. Design/methodology/approach – This article presents a case study of how a medium-size academic library without a designated scholarly communications librarian or office presented a series of open access (OA) training opportunities for the liaison librarians in preparation for the official launch of the institutional repository and the campus' inaugural participation in OA week. Findings – The multiple opportunities to engage with the topics in diverse ways resulted in librarians being more comfortable with discussing OA with their departmental faculty. Opinions of OA were changed as a result of attending the events. Participants found the activities to be useful and were engaged enough with the topic to ask for specific areas where they would like more training opportunities. Look to other colleagues both on campus and in the broader region to tap their expertise or explore professional organizations or free webinars. Taking the initiative to organize events that require minimal effort can have a big impact. Practical implications – Librarians have limited opportunity for in-depth training to gain new competencies and re-tool their skills to match current demands; this article demonstrates that utilizing internal expertise to provide a variety of training can positively impact participants' attitudes and confidence. Originality/value – This article presents methods and rationale for librarians to facilitate similar professional development opportunities for building new scholarly communication competencies in support of the emerging research and scholarly publishing trends.